Nivel de resolución de problemas de capacidades de adición y substracción mediante el método de singapur en estudiantes de segundo grado de la Institución Educativa Primaria Nº 60793 Túpac Amaru, Iquitos 2021 - Sanchez Ahuanari, Blanca Luz (2022)
The main purpose of the research was to describe the level of problem solving of addition and subtraction abilities using the Singapore method in second grade students of the Primary Educational Institution No. 60793 Tupac Amaru in the city of Iquitos in the 2021 school year, for this purpose, the results obtained from the specific objectives are also analyzed. As a methodology, the type of descriptive research was used with a non-experimental, cross-sectional, field design and with one variable. The population and sample of the investigation were 56 primary school students. To obtain the data, the survey was used as a technique and a test based on the Singapore method, which was previously validated by expert judgment. The findings show that the level of resolution of problems of addition and subtraction abilities after applying the test with the Singapore method in the second-grade students of the Primary Educational Institution No. 60793 Tupac Amaru is high at 3.6% (Expected achievement), while 78.6% are at the average level (In process) and 17.9% at the low level (Beginning).